Analysis of Metaphor in The Song “Helena” by My Chemical Romance - Bonifasius Nathanael Adi Nugraha; Ni Ketut Widhiarcani Matradewi; I Komang Sumaryana Putra (CV. Ulil Albab Corp, 2023)
The goal of this study is to identify the of figurative language and the meanings they express in the lyrics of My Chemical Romance's song Helena. Two theories are used in this study. Knickerbocker and Reninger's (1963) theory of figurative language serves as the first theory, and Leech's (1981) theory of meaning serves as the second. The information was derived from My Chemical Romance's song